Combined endonasal and eyelid approach for management of extensive frontal sinus inverting papilloma. (13th April 2017) - Albathi, Monirah; Ramanathan, Murugappan; Lane, Andrew P.; Boahene, Kofi D. O.
Abstract : Objectives: Sinonasal inverting papilloma (IP) is a benign but locally aggressive mucosal neoplasm with a high recurrence rate. Extension into the frontal sinus presents surgical challenges for endonasal resection. This study presents an orbitofrontal approach for managing extensive IP. Study Design: Case series. Methods: Four patients seen between 2012 and 2016 with biopsy‐proven IP with lateral frontal sinus extension underwent a combined endonasal and transpalpebral approach for tumor resection. Patient demographic data, preoperative characteristics, imaging, and follow‐up data were compiled through retrospective chart review. Patients were selected for this approach when the tumor extended to the posterior frontal sinus wall, lateral frontal sinus recess, and orbit. Tumors were first approached endonasally until the frontal recess was reached. A Draf IIB or Draf III procedure was then performed to gain better exposure. Orbitofrontal exposure was achieved through an upper eyelid incision. Miniorbitofrontal craniotomy window was designed based on tumor location. Resection of the frontal and orbital extension was enhanced by endoscopic‐assisted dissection through the orbitofrontal window. Results: The transpalpebral approach provided access to all walls of the ipsilateral frontal sinus, the intersinus septum, and the medial aspect of the contralateral sinus. Complete tumor resection was achieved in all patients. There were no orbital complications, no visible eyelid asymmetry or scarring, and all patients had preserved forehead sensation. There were no recurrences on follow‐up. Conclusion: Combining a transpalpebral orbitofrontal craniotomy with the endonasal approach allows complete resection of invasive IP with extension into the frontal sinus. This is achieved with great cosmetic results. Level of Evidence: 4. Laryngoscope, 128:3–9, 2018